Alain Badiou’s Suturing of the Law to the Event and the State of Exception - Calcagno, Antonio (Journal of French and Francophone philosophy, 2016)
This article questions whether we can posit a more radical desuturing of the law from the event: Can radical shifts in law produce events? Can the law itself be an event, thereby conditioning the very nature of the event itself, creating a new subjectivity and a new time?  I would like to argue that the law can do so. How? Badiou begins “The Three Negations” by discussing the work of the German jurist Carl Schmitt (TN 1877). I would like to argue that the state of exception, as elaborated by Carl Schmitt, can serve as the willed decision of a sovereign that brings about an event.  We can understand the sovereign as a kind of legal subject that has the force to bring about a new event, rupturing with an established order and introducing a new form of subjectivity and time.